Historical overview of breastfeeding in Slovenia - Mičetić Turk Dušanka; Turk, Eva; Šikić Pogačar Maja (Acta Medico-Biotechnica, 2021)
Breastfeeding is an optimal nutrition that supports the healthy growth and development of infants. Numerous indicators suggest the benefits of breast– feeding to child health during infancy and later in life. Although breastfeeding is highly recommended by European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN), American Academy of Pediatrics (AAP), World Health Organisation (WHO), United Nations International Children’s Emergency Fund (UNICEF) and many others, it may not be always possible, suitable or adequate (i.e. in some metabolic disorders). Human milk was and still is the best food for nearly all infants. Wet nursing was the safest and most common alternative to breastmilk before bottles with nipples and infant milk formulas were invented. Although parents are responsible for decisions on breastfeeding their infants, the role of health care workers, including pediatricians, is to protect, promote, and support breastfeeding. In this article, a historical overview of breastfeeding in Slovenia is presented with a description of the socioeconomic situation in the past.